Los recursos didácticos como medios potencializadores aprendizaje significativo de las matemáticas en los niños y niñas del cuarto y quinto año de educación básica de la Escuela Víctor Manuel Arregui de la parroquia La Asunción cantón Chimbo provincia Bolívar en el periodo 2011-2012 - Echeverría Vega, Carlos Benigno (2012)
This Labor Grade allows to know the different materials (materials) that teachers should use in our daily educational classes for the different areas of study, changing the conceptual schema to the constructivist or traditionalist. The activity of the master, that is, teaching is considered as an activity of mediation between culture in its broadest sense, represented in the curriculum, and student. Therefore, the teacher, through the activity of teaching is to facilitate student learning, for which it has different elements, means or resources, which help to enable their work of cultural mediation. Such support the teaching material is all that natural or artificial object that produces a significant learning on the student. In the global scope of the thesis is composed of a first part dealing with general aspects of an introduction, where synthetically develop basic elements concerning the pedagogical and didactic, especially with regard to the use of teaching resources in the area of mathematics, leading to these issues led me to develop activities that implicitly specifies the reason for the task investigated. In Chapter I, the reader may find the theories underlying the research work, it examines the Pedagogical Theories. Psychological and Cognitive, like constructivist theory in order to get an overview of the complexity of knowledge that is taught in education in relation to the processes of learning and inter-related methods and techniques the teacher uses in the influence of the classroom and teaching resources in cognitive development and production of meaningful learning. Therefore requires a permanent training for the teacher to fulfill its proper function to generate a pleasant learning environment that allows the combination of theory with practice, allowing students' cognitive development and production of meaningful learning, discarding thus, those traditional patterns and repetitive, giving way to a true knowledge construction through proper implementation of teaching resources and the use of active methodologies and practices. It emphasizes the importance, usefulness and classes teaching resources more conducive for the treatment of mathematics and creative motivations and causes it. Our research work presents suggestions for the proper management of teaching resources structured and unstructured for the area of mathematics, designed to ensure the gradual shift from concrete to abstract, gradually moving from the notional is how the student thinks Until this very thought has reached a certain logic, thanks to their cognitive understanding that the learning by doing, students construct their own knowledge and internalize significant knowledge that will be useful in their daily lives and when this require it. Must always be borne in mind that learning mathematics involves two activities, one includes reflection and understanding of events, situations or mathematical problems with a sense of the relationships that link the facts bringing into play essentially cognitive development Thanks to the rationale, and the other is to exploit their technical and operational knowledge in finding solutions. In Chapter II is brought into consideration the methodology used in the research process, this is the type of investigation, procedure, sample and data collection technique. I noted that the investigation was based on the inductive and deductive methods, under which the application gave me the most appropriate procedure according to the characteristics that enabled me to discover, understand and explain the behavior of selected population universe, who applied the survey and data collection technique. It is noteworthy that it was necessary to application of any formula for determining the sample because it is a very small population universe. CHAPTER III corresponds to the analysis and interpretation of results obtained in implementing the respective survey, they were tabulated once represented in tables and plotted together with their statistical interpretation respectively. Subsequently conducted testing the hypothesis that helped me to develop conclusions and recommendations. It is necessary to indicate that one of the conclusions, and perhaps most important, is that which determines school teachers' Victor Manuel Arregui "of the Assumption parish, Cantón Chimbo, Bolívar Province require training for proper handling of teaching resources, which implies that such training should be developed, thus giving credence to the proposal made in this investigation. Finally in Chapter IV is applied to the proposal seeks to rectify a problem detected at the beginning of our investigation. The proposal is titled, "WORKSHOPS EDUCATIONAL RESOURCE FOR THE AREA OF MATHEMATICS." At the same find a variety of teaching resources accompanied by methodological suggestions and goals or profits of each of them, because everyone responds to guidelines aimed at developing the capacities and potential of students tending achieving significant learning from the appropriate mix of theory and practice of social reality environments for a genuine cognitive development.